Utility of Tc-99m DTPA Hybrid SPECT/CT Cisternography in the Detection of Occult Postoperative CSF Fistula in an Infant with Lipomeningomyelocele: A Diagnostic Challenge and Technical Considerations - I Kadek Herry Hermawan; Achmad Hussein Sundawa Kartamihardja; Trias Nugrahadi; Reza Rinaldy Harahap (HM Publisher, 2026)
Background: Lipomeningomyelocele represents a complex spectrum of closed spinal dysraphism where surgical repair is frequently complicated by cerebrospinal fluid leakage. While overt fistulas are clinically apparent, occult or intermittent leaks in the pediatric population pose a severe diagnostic challenge. Magnetic resonance imaging, despite being the anatomical gold standard, frequently fails to distinguish active extravasation from postoperative seroma or edema due to overlapping signal intensities. This study evaluates the diagnostic superiority of Tc-99m DTPA Hybrid SPECT/CT cisternography in resolving this dilemma. Case presentation: A 5-month-old female underwent resection of a large lumbosacral lipomeningomyelocele. Postoperatively, she developed persistent, clear fluid discharge from the incision, suggestive of a fistula, yet initial surgical re-exploration was inconclusive. The patient underwent radionuclide cisternography using 37 MBq of intrathecal Tc-99m DTPA. Standard planar scintigraphy at 1 hour and 3 hours was equivocal due to background renal activity. However, Hybrid SPECT/CT performed at 3 hours precisely localized an abnormal radiotracer tract extending from the thecal sac at L5 into the right multifidus muscle, a finding invisible on conventional imaging. Conclusion: The integration of physiological flow data from scintigraphy with the anatomical specificity of low-dose CT allows for the detection of slow-flow, occult leaks that evade MRI. In infants with distorted post-surgical anatomy, Hybrid SPECT/CT should be elevated from a problem-solving tool to a primary diagnostic modality when clinical suspicion persists. The technique facilitates targeted repair, minimizing morbidity in this vulnerable population.